Peach polyphenol and carotenoid content as affected by frozen storage and pasteurization - Oliveira, Ana L. (2017)
The profile of polyphenol and carotenoid of peach were analysed on fresh fruits, immediately after freezing or after pasteurization, and during frozen storage at -20 ºC for 360 days. Freezing did not affect the concentration of polyphenols or carotenoids. Pasteurization of fresh and frozen samples induced an increase in the extractability of chlorogenic acid (38% and 24%) and of zeaxanthin (336% and 127%) and a decrease of lutein (22% and 56%) and b-cryptoxanthin (32 and 51%). Total antioxidant capacity and total phenolic content changed by less than 20% after frozen storage for 360 d. However, total carotenoid content decreased 41% and 48% in unpasteurized and pasteurized samples, after the same storage period. Long term storage induced an increase in the extractability of (+)-catechin (47%) and zeaxanthin (90%) and a decrease in neochlorogenic acid (59%), chlorogenic acid (39%), quercetin-3-glucoside (21%), lutein (24%) and b-cryptoxanthin (40%). Pasteurization of frozen samples promoted a decrease in the concentration of neochlorogenic acid (91%), chlorogenic acid (87%) and quercetin-3-rutinoside (71%) and increase in lutein (16%), b-cryptoxanthin (42%) and b-carotene (31%). Peach should be stored for periods no longer than 230 d, since pasteurization after that, induced a higher decrease in neochlorogenic, chlorogenic acids and quercetin-3-rutinoside content.